1997
DOI: 10.1002/(sici)1097-4695(19970605)32:6<627::aid-neu7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of process formation during differentiation of tectal neurons in embryonic zebrafish

Abstract: Neurons acquire their distinct shapes after passing through many transitional stages in early development. To reveal the dynamics and spatiotemporal sequence of process formation in situ, the growth of neurons in the optic tectum of live zebrafish embryos (54 to >100 h old) was monitored using time‐lapse videorecordings. Neurons were labeled by injecting the fluorescent vital dye DiO into the cell‐rich layer of the developing tectum in 50‐ to 70‐h‐old embryos. In phase 1, tectal neurons possess an apical “prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Studies examining neuronal development in the tectum have typically utilized methods that label a broad cross-section of tectal neurons (Kaethner and Stuermer, 1997; Niell and Smith, 2005; Sato et al, 2007; Scott and Baier, 2009). Although these studies have revealed general mechanisms common to many different cell types, a complete understanding of tectal circuit function will only be attained when we understand the structure and connectivity of specific neuron types.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining neuronal development in the tectum have typically utilized methods that label a broad cross-section of tectal neurons (Kaethner and Stuermer, 1997; Niell and Smith, 2005; Sato et al, 2007; Scott and Baier, 2009). Although these studies have revealed general mechanisms common to many different cell types, a complete understanding of tectal circuit function will only be attained when we understand the structure and connectivity of specific neuron types.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, nicotinic receptors' density in the superior colliculus (optic tectum in the zebrafish) is very dense (Clarke et al 1985). The optic tectum, positioned much like the neocortex in mammals and constituting a considerable portion of the zebrafish brain (Wullimann et al 1996), is the major processing area for visual processing in zebrafish (Kaethner and Stuermer 1997). Zebrafish express functional β3, α2, and α7 nicotinic receptors and these receptors show a high degree of similarity with mammalian nicotinic receptors (Zirger et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, nicotinic receptor density in the optic tectum (superior colliculus) is very high (Clarke et al 1985). The optic tectum is the major processing area for visual processing in zebrafish (Kaethner and Stuermer 1997) and constitutes a considerable portion of the zebrafish brain, positioned much like the neocortex in mammals (Wullimann et al 1996). Further research is necessary to determine the possible role of nicotinic receptors in the zebrafish optic tectum for cognitive function.…”
Section: Discussionmentioning
confidence: 99%